Civic Education Teachers’ Strategies for Preventing Violence at State Junior High School 2 Bajeng Barat - Rahmia, Rahmia; Umar, Firman; Khiyarudami, Khala Iva; Bakhtiar, Bakhtiar (Actual Insight, 2025)
This study aims to examine: (1) the efforts made by Civic Education teachers to prevent violence during the learning process, and (2) the inhibiting factors that affect those efforts. This research employs a qualitative approach with data collection techniques including interviews, observations, and documentation. The informants consist of two Civic Education teachers and seven students from State Junior High School 2 Bajeng Barat. The findings indicate that teachers prevent violence through class agreements, giving advice, creating a conducive learning atmosphere, and providing positive reinforcement. The inhibiting factors include diverse student characteristics, students’ lack of understanding regarding violence, family environmental background, and limited school facilities. Preventing violence requires the active involvement of all school stakeholders, including participatory engagement from students. Teachers are also expected to possess effective communication and classroom management skills. These findings are expected to serve as input for the development of learning strategies that are inclusive, supportive, and free from violence.